Laser-Induced Forward Transfer of Silver Nanoparticles for a Black Metal Absorber - Li, Ruo-Zhou; Guo, Lvjiu; Liu, Leilei; Yang, Mingqing; Fang, Yuming; Yu, Ying; Yan, Jing (Frontiers in Physics, 2022)
Plasmonic nanostructures emerged as an appealing approach for black metal absorbers (BMAs) to provide significant light absorption. We present the simple and rapid fabrication of BMAs using laser-induced forward transfer of silver nanoparticles (AgNPs). Randomly distributed plasmon silver nanostructures with multiscale were produced simultaneously during laser transfer, providing significant light absorption and antireflection features. The laser-transferred BMAs exhibit excellent absorption capacity of a value over 96%, and a minimum reflection of 0.38%. A high scanning speed of 10 m/s was used that can complete the LIFT process within 2 s for a 1 cm2 area. The nearfield light confinement is discussed in terms of the morphology of the obtained nanostructures. Photothermal conversion with macroscale temperature rising was demonstrated for the laser-induced BMAs. The results indicated that laser-induced forward transfer (LIFT) is an effective method for the industrial production of BMAs with excellent absorption capacity.